SEJARAH PERKEBUNAN GAMBIR DI KABUPATEN LINGGA (1970-2015) - yuniva, fira; Ahmal, Ahmal; Asril, Asril (Jurnal Dinamika Sosial Budaya, 2022)
Plantations in Indonesia has been known since the arrival of the Dutch colonial in Indonesia Although the glory of gambir in riau islands ended in 1970, but for Lingga Regency the success of gambir plantations persisted in that year, evidenced by one of the Tioghoa residents named Hainan opened gambir ward in Lingga Regency located in Kudung Village. The method used is the historical research method. According to Louis Gottschalk, the historical method is the process of critically testing and analyzing records and relics of the past. With the method of history can also be reconstructed as many events as the human past. The 1970s and 1990s were a lucrative year for Mok ciu keng's and Ameng gambir plantations where the family's plantations were able to penetrate the export market to Japan.